Effect of motivational interviewing on gestational weight gain and fetal growth in pregnant women with type 2 diabetes - Peter Damm; Björg Ásbjörnsdóttir; Marianne Vestgaard; Lene Ringholm; Lise Lotte Torvin Andersen; Dorte Møller Jensen; Elisabeth R Mathiesen (BMJ Open Diabetes Research & Care)
Objective To study how lifestyle coaching with motivational interviewing to improve adherence to healthy eating affects gestational weight gain and fetal growth in pregnant women with type 2 diabetes in a real-world setting.Research design and methods A cohort study including a prospective intervention cohort of consecutive, singleton pregnant, Danish-speaking women with type 2 diabetes included between August 2015 and February 2018 and a historical reference cohort included between February 2013 and August 2015. The intervention consisted of a motivational interviewing to improve adherence to healthy eating in addition to routine care. The reference cohort received routine care only. The main outcomes were gestational weight gain and large for gestational age (LGA) infants.Results Ninety-seven women were included in the intervention cohort and 92 in the reference cohort. Pre-pregnancy body mass index (32.8±6.9 kg/m2 vs 32.4±7.4 kg/m2, p=0.70), gestational weight gain (9.2±5.8 kg vs 10.2±5.8 kg, p=0.25), HbA1c in early pregnancy (6.7%±1.1% vs 6.5%±1.3% (50±12 mmol/mol vs 48±14 mmol/mol), p=0.32) and late pregnancy (5.9%±0.5% vs 6.0%±0.6% (41±6 mmol/mol vs 42±7 mmol/mol), p=0.34) were comparable in the two cohorts. LGA infants occurred in 20% vs 31%, p=0.07, respectively, and after adjustment for maternal characteristics 14% vs 27% delivered LGA infants (p=0.04). Birth weight z-score was 0.24±1.36 vs 0.61±1.38, p=0.06.Conclusions Motivational interviewing to improve adherence to healthy eating in addition to routine care in pregnant women with type 2 diabetes tended to reduce fetal overgrowth without major effect on gestational weight gain. Further studies investigating the cost-benefit of enhancing motivation are needed.Trial registration number NCT02883127.